Common presentations of patients in General Practice Clinic at Patan Academy of Health Sciences - Shakya, Abishesh; Maharjan, Prativa; Yadav, Chadani Salmalee; Shrestha, Yashmin; Bhushal, Priya; Mahato, Rahul; Subedi, Rajan (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Introduction: General practice clinic sees wide variety of patients. To improve the quality of care and for uniformity a protocol based approach should be applied. So, this study is designed to see the common presentations in the patient coming to general practice clinic.Methods: This is a cross sectional study that was carried out from June 2014 to May 2015.Data was evaluated each month to see the common presentation.Results: Total data collected in six month from general practice out patient was 2,120 which is 1.79% of total OPD visit. Out of this 766 (35.9%) were male and 1,362 (64.1%) were female. The most common presenting symptom in the OPD was pain abdomen 19.38% in which acute gastritis was the most common cause. Fever (9.29%) the second most common symptom. Cough (6.79%) was the third common presenting symptom. Fourth most common symptom was amenorrhea (6.13%) , finally the fifth common symptom was headache and the most common cause was tension headache (3.77%).Conclusion: Pain abdomen is the most common cause of patient presenting to emergency out of which gastritis is the most common.